Accommodating landscape-scale shocks: Lessons on transition from Cape Town and Puerto Rico. Issue 102 (June 2019) - Simpson, Nicholas Philip
Highlights: Public planning failed to anticipate the severity of unprecedented environmental disruptions. Private actors explore alternative pathways to water and energy security. Utility scale providers of public goods push back against off-grid behaviours and technologies. Environmental shocks open disruptive niches for new technologies to cascade. Abstract: Landscape-scale shocks, in the forms of Hurricane Maria and an unprecedented drought, have provided significant disruptions to the respective centrally designed water and energy networks of Puerto Rico and Cape Town. Despite a number of contextual differences, this article considers what can be learnt from the two cases as they present significant similarities in off-grid responses and adaptation endeavours by a range of key actors. The cases illustrate how these large and centrally planned utility providers were ill-equipped to perceive and appropriately respond to both the landscape-scale shocks and the associated social and technological disruptions which they brought about. The cases illustrate similarities in how back-burner technologies can cascade, at unprecedented speeds, to fill polycentric niches created by failure of centralised service delivery. A fundamental lesson, which illustrates the challenges to transition to decentralised and off-grid systems, is the push-back from a disrupted regime. The cases demonstrate centralising endeavours by utilities to reconfigure and recover from both the environmental shock as well as the novel governance arrangements of economic, social and technological shifts which occurred.